The Development Potential of Micro-Hydro Distillation of Ylang-Ylang (Cananga odorata) Essential Oil as a Nature Conservation Effort in Ngasem Village, Malang Regency. - Afriandi Setiawan; Zainal Abidin; Dyah Pitaloka; Anggraeni Hadi Pratiwi; Rif’an Khasbilazizi; Aprilia Dwi Puspitasari (JURNAL AGRIMENT, 2025)
Ngasem located on the slopes of Mount Kawi, is recognized as a cultural tourism destination in Malang. Cananga flower is in high demand for cultural tourism purposes in this area, indicating its potential to become a flagship commodity that has traditionally relied on local supply. Cananga tree also possesses ecological value, contributing to nature conservation. Furthermore, the flower contains essential oils that can be developed to enhance the value of agricultural products. Micro-hydro distillation represents an innovative method for optimizing essential oil extraction. As a result, the community of Ngasem has come to understand the added value potential of Cananga flowers, positioning this plant as a primary commodity with significant ecological value in the pursuit of sustainable nature conservation. The results of the study indicate that the micro-hydro distillation method is effective in extracting essential oils, with optimal sample collection times ranging from 60 to 90 minutes. Longer durations do not significantly impact the quantity of oil produced. Therefore, by disseminating information to the community about the use of micro-hydro distillation to enhance the added value of Cananga flowers in Ngasem Village, the potential for developing Cananga as a flagship commodity with ecological, economic, and social value can be increased, thereby supporting sustainable nature conservation management. Keywords: conservation, Cananga odorata, atsiri oil, micro-hydro distillation